Anchoring households' inflation expectations when inflation is high - Giang Hong Nghiem; Lena Dräger; Ami Dalloul (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2024)
This paper explores communication strategies for anchoring households' mediumterm inflation expectations in a high inflation environment. We conducted a survey experiment with a representative sample of 4,000 German households at the height of the recent inflation surge in early 2023, with information treatments including a qualitative statement by the ECB president and quantitative information about the ECB's inflation target or projected inflation. Inflation projections are most effective, but combining information about the target with a qualitative statement also significantly improves anchoring. The treatment effects are particularly pronounced among respondents with high financial literacy and high trust in the central bank.
Keywords: E52; E31; D84; 330; Anchoring of inflation expectations; central bank communication; survey experiment; randomized controlled trial (RCT)